The Influence of Traditional Religious Beliefs on Public Attitudes Toward Environmental Conservation in Rivers State, Nigeria - Wachukwu, Chikodi Josiah; Kii, Pius Barinaadaa (NIU Journal of Humanities, 2025)
This study investigates how traditional religious beliefs shape public attitudes toward environmental conservation in Rivers State, Nigeria. Grounded in environmental sociology and cultural ecology theories, the research explores the association between indigenous belief systems and community engagement in environmental practices. Using a structured questionnaire administered to 400 respondents across three senatorial zones, data were analyzed using descriptive statistics and inferential tests (mean scores and independent t-tests). Findings revealed that traditional beliefs significantly influence environmental perceptions and behaviors, with variations across religious adherence and demographic categories. The study concludes that integrating cultural values into conservation strategies can enhance public engagement and sustainability efforts. Keywords: Traditional Beliefs, Environmental Conservation, Public Attitudes, Indigenous Knowledge, Rivers State, Nigeria